Strengthening Pre-Service Teachers’ Competence in Implementing Local Wisdom-Based Learning Methods at MTsN 7 North Aceh - Nuriman Nuriman; Erlidawati Erlidawati; Hayatul Muna Hayatul Muna; Fauzi Fauzi; Richa Meliza (Jurnal Solusi Masyarakat (JSM), 2026)
This Community Service Program (CSP) aims to strengthen pre-service teachers’ competence in implementing local wisdom-based learning at Madrasah. The program responds to the gap between pre-service teachers’ knowledge of Acehnese local wisdom and their ability to transform cultural values into contextual and meaningful learning experiences. A participatory and experiential learning approach was employed through five stages: needs assessment, competency strengthening, instructional design, microteaching, and supervised classroom practice, followed by reflection and mentoring. Program activities focused on strengthening local wisdom literacy, pedagogical content knowledge, instructional design, teaching practice, and reflective competence. Participants were trained to identify educational values embedded in local wisdom, including Hadih Maja, meuseuraya, respect for parents and teachers, and traditions of deliberation, and integrate these values into learning objectives, materials, activities, methods, and assessment. Program effectiveness was evaluated through pre-test and post-test comparisons, teaching-performance observation, assessment of instructional products, and participant reflection. The expected outcomes include improved pedagogical competence, practical instructional skills, and the production of contextual learning materials. The program also promotes a sustainable model through a local wisdom-based learning resource bank and community of practice. The program seeks to develop culturally responsive pre-service teachers capable of transforming local wisdom into authentic and meaningful learning experiences